2008
DOI: 10.1021/jp8009436
|View full text |Cite
|
Sign up to set email alerts
|

Photodissociation of Iron Oxide Cluster Cations

Abstract: Iron oxide cluster cations, Fe(n)O(m)(+), are produced by laser vaporization in a pulsed nozzle cluster source and detected with time-of-flight mass spectrometry. The mass spectrum exhibits a limited number of stoichiometries for each value of n, where m > or = n. The cluster cations are mass selected and photodissociated using the second (532 nm) or third (355 nm) harmonic of a Nd:YAG laser. At either wavelength, multiple photon absorption is required to dissociate these clusters, which is consistent with the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
97
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(109 citation statements)
references
References 196 publications
(195 reference statements)
11
97
1
Order By: Relevance
“…This finding is in favorable agreement with previous dissociation patterns of Fe x O y + clusters. Photodissociation, collision induced dissociation as well as temperature-programmed desorption experiments revealed the preferred formation of stoichiometric fragments for Fe x O y + (x > 2) while the smaller clusters tend to fragment into Fe + and FeO 2 + [25][26][27][28]. Using bare iron powder changes the color of the targets to a shiny gray (cf.…”
Section: Resultsmentioning
confidence: 99%
“…This finding is in favorable agreement with previous dissociation patterns of Fe x O y + clusters. Photodissociation, collision induced dissociation as well as temperature-programmed desorption experiments revealed the preferred formation of stoichiometric fragments for Fe x O y + (x > 2) while the smaller clusters tend to fragment into Fe + and FeO 2 + [25][26][27][28]. Using bare iron powder changes the color of the targets to a shiny gray (cf.…”
Section: Resultsmentioning
confidence: 99%
“…Collision-induced photodissociation experiments can further establish the relative stability of mass-selected metal-oxide cluster ions. [47,48]. Contrary to the conventional understanding that the structure of atomic clusters usually differ from the bulk constituents of which they are comprised, Sun et al [51] showed that even a dimer of tungsten oxide (WO 3 ) 2 possesses bulk-like features and geometry of a small cluster containing only 4 tungsten and 12 oxygen atoms bears the hallmarks of crystalline tungsten oxide, Fig.…”
Section: Transition Metal-oxide Clustersmentioning
confidence: 99%
“…Seminal studies by Castleman and coworkers [44][45][46] and Duncan's [47][48][49][50] groups on oxide clusters of V, Fe, Co, Zr, Nb, etc. have shown dramatic patterns with specific stoichiometries throughout the mass range and compositions not found in bulk solids.…”
Section: Transition Metal-oxide Clustersmentioning
confidence: 99%
“…Second, as the laser irradiation in our work was high and reached 9 ϫ 10 10 W/cm 2 , the central plasma temperature was estimated to be 9 eV at 10 ns and 4.5 eV at 100 ns after laser radiation [35][36][37]. Most of the neutral clusters were likely to be dissociated than be ionized at the high temperature (e.g., bond energies for the loss of O and O 2 from iron oxide clusters were between 3 and 5 eV [38], while ionization potentials were 7 to 8 eV for the clusters [39]). As a result, particles at the central part of the expansion plasma Ϫ123…”
Section: Evaluation Of Laser Wavelengthmentioning
confidence: 99%